In Vivo Impact of Met221 Substitution in GOB Metallo-β-Lactamase - Moran Barrio, Jorgelina (2012)
Metallo- -lactamases (M Ls) represent one of the main mechanisms of bacterial resistance against -lactam antibiotics. The elucidation of their mechanism has been limited mostly by the structural diversity among their active sites. All M Ls structurally characterized so far present a Cys or a Ser residue at position 221, which is critical for catalysis. GOB lactamases stand as an exception within this picture, possessing a Met residue in this location. We studied different mutants in this position, and we show that Met221 is essential for protein stability, most likely due to its involvement in a hydrophobic core. In contrast to other known M Ls, residue 221 is not involved in metal binding or in catalysis in GOB enzymes, further highlighting the structural diversity of M Ls. We also demonstrate the usefulness of protein periplasmic profiles to assess the contribution of protein stability to antibiotic resistance.